2017
DOI: 10.1007/s11192-016-2238-1
|View full text |Cite
|
Sign up to set email alerts
|

Citation algorithms for identifying research milestones driving biomedical innovation

Abstract: Scientific activity plays a major role in innovation for biomedicine and healthcare. For instance, fundamental research on disease pathologies and mechanisms can generate potential targets for drug therapy. This co-evolution is punctuated by papers which provide new perspectives and open new domains. Despite the relationship between scientific discovery and biomedical advancement, identifying these research milestones that truly impact biomedical innovation can be difficult and is largely based solely on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…The comparison showed that the expert view discovered similar historical roots as the RPYS. A similar result has been presented by Comins and Leydesdorff (2017). They assessed whether the results of RPYS ‘converge with expert opinions on research milestones driving biomedical innovation in the treatment of Basal Cell Carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…The comparison showed that the expert view discovered similar historical roots as the RPYS. A similar result has been presented by Comins and Leydesdorff (2017). They assessed whether the results of RPYS ‘converge with expert opinions on research milestones driving biomedical innovation in the treatment of Basal Cell Carcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…We used Patent Citation Spectroscopy-originally developed as Reference Publication Year Spectroscopy for studying landmarks and milestones in scientific literature (Comins & Leydesdorff, 2017;Thor, Marx, Leydesdorff, & Bornmann, 2016)-to patent literature classified into the nine Y-subclasses of CPC that describe material photovoltaic technologies. In five of the nine cases, we found corroborating evidence for the foundational character of the patent indicated by the routine.…”
Section: Discussionmentioning
confidence: 99%
“…While citation analysis penetrates different disciplines, such as economics and management (Laengle et al, 2017;Merigo & Yang, 2017), sociology (Moed, Luwei, & Nederhof, 2002;White, Boell, & Yu, 2009;White, 2015), and biomedicine (Bornmann & Daniel, 2006;Comins & Leydesdorff, 2017;Garfield, 1991), highlycited analysis shows its unique advantages to generate interesting and meaningful exploration in different discipline areas, where we mention that Bornmann and Leydesdorff (2015) did research in the domain of top-cited papers to investigate the development of the BRICS countries and scientific excellence.…”
Section: Journal Of Data and Information Sciencementioning
confidence: 99%